The Fran with four brains - Benton, Jim (Benton, Jim. Franny K. Stein, mad scientist, 2006)
With so much on her plate, like creating monsters out of meat by-products and dealing with overgrown babies, mad scientist Fran decides that the only way to get all her tasks done is to create Franbots, steel-plated duplicates of herself with minds of their own.